2018
DOI: 10.22159/ajpcr.2018.v11i10.25097
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Some Plants in Nainamalai Foothill, Eastern Ghats, Namakkal

Abstract: Objectives: This study was designed to document some medicinal plants in Nainamalai foothill.Methods: The plants were collected from different sites of the hill area, identified by their local names with the help of villagers while walking through the vegetation. The photographs of these plant species were taken during the field visits.Results: Plant survey at Ninamalai foothill has documented a total of 124 plants. Among 124 species surveyed, 123 were angiospermic plants and one pteridophytic plant. Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Ethnobotanical surveys conducted in different parts across Asia contribute to the existing repository of traditional ethnobotanical knowledge. For example, Keo et al (2018) documented 50 species of medicinal plants in Cambodia that have been customarily used to treat common ailments while the survey of Sharmila et al (2018) on some plant species in Nainamalai Foothill in the Eastern Ghats recorded a total of 124 plants used in a variety of medicinal applications. Meanwhile, the study of Taek et al (2018) reported several ethnomedicinal plants as treatment for malaria in Malaka, West Timor.…”
Section: Introductionmentioning
confidence: 99%
“…Ethnobotanical surveys conducted in different parts across Asia contribute to the existing repository of traditional ethnobotanical knowledge. For example, Keo et al (2018) documented 50 species of medicinal plants in Cambodia that have been customarily used to treat common ailments while the survey of Sharmila et al (2018) on some plant species in Nainamalai Foothill in the Eastern Ghats recorded a total of 124 plants used in a variety of medicinal applications. Meanwhile, the study of Taek et al (2018) reported several ethnomedicinal plants as treatment for malaria in Malaka, West Timor.…”
Section: Introductionmentioning
confidence: 99%